Noggin proteins are multifunctional extracellular regulators of cell signaling. Issue 1 (31st March 2022) - Karunaraj, Prashath; Tidswell, Olivia; Duncan, Elizabeth J; Lovegrove, Mackenzie R; Jefferies, Grace; Johnson, Travis K; Beck, Caroline W; Dearden, Peter K
Abstract: Noggin is an extracellular cysteine knot protein that plays a crucial role in vertebrate dorsoventral patterning. Noggin binds and inhibits the activity of bone morphogenetic proteins via a conserved N-terminal clip domain. Noncanonical orthologs of Noggin that lack a clip domain ("Noggin-like" proteins) are encoded in many arthropod genomes and are thought to have evolved into receptor tyrosine kinase ligands that promote Torso/receptor tyrosine kinase signaling rather than inhibiting bone morphogenic protein signaling. Here, we examined the molecular function of noggin / noggin-like genes ( ApNL1 and ApNL2 ) from the arthropod pea aphid using the dorso-ventral patterning of Xenopus and the terminal patterning system of Drosophila to identify whether these proteins function as bone morphogenic protein or receptor tyrosine kinase signaling regulators. Our findings reveal that ApNL1 from the pea aphid can regulate both bone morphogenic protein and receptor tyrosine kinase signaling pathways, and unexpectedly, that the clip domain is not essential for its antagonism of bone morphogenic protein signaling. Our findings indicate that ancestral noggin/noggin-like genes were multifunctional regulators of signaling that have specialized to regulate multiple cell signaling pathways during the evolution of animals.